Determinants of merger review decisions: an assessment of the Brazilian antitrust authority\'s capabilities and the influential role of antitrust commissioners - Moran, Marcio Roberto (2015)
Merger reviews are institutionalized and customized analyses of mergers and acquisitions by antitrust authorities which result in approvals or disapprovals of the strategic intents of firms. In view of the wide variety of agents whose lives may be changed by a merger review, the fact that different stakeholders might induce a government intervention on a particular deal, and the central role of antitrust commissioners in this context, the general aim of this thesis is to examine the determinants of merger review decisions, but particularly those related to commissioners\' personal attributes, values and interests. Additionally, some structural and procedural issues contained in the antitrust regulatory sphere as well as control variables related to other perspectives of analysis are included as part of this empirical analysis. To achieve the mentioned general objective and other specific goals, a unique dataset was built that covers a fourteen-year period of competition regulation in Brazil. The sample of this study comprises 30,543 votes by 36 different panel members on 5,091 transactions examined through ordered probit models. This thesis, mainly, reveals that \'political ideology\', \'prior work experience in the public service\' and \'human capital\' of antitrust commissioners, in addition to the size of commissions\' voting panels, affect consistently merger review verdicts. In short, under the PSDB presidential administration, for example, transactions were less challenged in Brazil. Regarding the \'public service experience\', commissioners who have predominant prior job or professional association in Education, Health and Social areas, inversely to \'political ideology\', increase the likelihood of high levels of intervention in private deals. Additionally, commissioners\' accumulated skills and knowledge - the \'human capital\' - also affect positively law enforcement on merger reviews. The implications of this particular contribution to public administration follow the same path of \'public service experience\': if societies do not pressure politicians to improve public service, considering not only a remarkable knowledge in Law or Economics to appoint a commissioner, but having a broader view of individuals\' motivations and claims, interferences between \'concepts, principles and norms\' stated in laws, and law enforcement will continuously occur. The last consistent result shows that the likelihood of the Brazilian authority to impose significant changes to firms decreases the greater the voting panel. Thus, this thesis suggests to antitrust policymakers that wide ranges of minimum and maximum quorum in voting panels must be avoided. To the best knowledge of this thesis author, there is not any past research that found such results. It means a unique contribution to the antitrust and management literatures.